Transformasi Pendidikan Islam di Era Digital: Antara Inovasi Teknologi dan Krisis Karakter - Ariyanto Ariyanto; Sukari Sukari (TSAQOFAH, 2026)
The transformation of Islamic education in the digital era is a consequence of advances in information technology that have changed learning systems, patterns of knowledge transmission, and students’ learning culture. Although technological innovation expands access to learning resources and improves learning effectiveness, the development of virtual spaces and algorithmic culture also presents challenges in the form of an instant culture of acquiring knowledge, declining ethical conduct in seeking knowledge, weak critical thinking skills in evaluating religious information, and a shift in scholarly authority from teachers to social media and digital algorithms. This study aimed to analyze the transformation of Islamic education in the digital era, examine the impact of technological innovation on learning, and identify the implications of algorithmic culture for students’ character development. The study employed a descriptive qualitative approach using library research through the analysis of various relevant sources. The results of the review showed that the transformation of Islamic education is characterized by changes in learning systems, patterns of knowledge transmission, and students’ learning culture. Technological innovation provides opportunities to improve the quality of Islamic education learning, but algorithmic culture also encourages the formation of instant, partial religious understanding with minimal verification. A character crisis has emerged because the internalization of Islamic values in the use of digital technology has not yet occurred optimally. This study concludes that strengthening Islamic digital literacy, developing innovative learning based on Islamic values, and implementing character education that emphasizes morality and ethical conduct are the main strategies for realizing a transformation of Islamic education that is adaptive to technological developments without losing its Islamic identity and values.